2015
DOI: 10.1017/psrm.2015.56
|View full text |Cite
|
Sign up to set email alerts
|

Coalition Governments and Party Competition: Political Communication Strategies of Coalition Parties

Abstract: Coalition parties have to reconcile two competing logics: They need to demonstrate unity to govern together, but also have to emphasize their own profile to succeed in elections. We argue that the electoral cycle explains whether unity or differentiation prevails. While differentiation dominates at the beginning and the end of the legislative term in close proximity to elections, compromise dominates the middle of the term when coalition governments focus on enacting a common policy agenda. To test our theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 43 publications
2
100
0
6
Order By: Relevance
“…In order to analyse the attention that political parties in Germany pay to different policy issues, we study the press releases published by their party groups in the German Bundestag (see also Sagarzazu and Klüver 2015). Press releases are an ideal data source to study the selective issue emphasis of political parties as we can trace the attention that parties pay to different policy issues on a daily basis, which constitutes a major advantage over election manifestos which are only published in election years.…”
Section: Measuring Issue Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to analyse the attention that political parties in Germany pay to different policy issues, we study the press releases published by their party groups in the German Bundestag (see also Sagarzazu and Klüver 2015). Press releases are an ideal data source to study the selective issue emphasis of political parties as we can trace the attention that parties pay to different policy issues on a daily basis, which constitutes a major advantage over election manifestos which are only published in election years.…”
Section: Measuring Issue Attentionmentioning
confidence: 99%
“…Second and more importantly, we rely on a novel dataset that was generated based on a quantitative text analysis of more than 40,000 press releases published by German political parties between 2000 and 2010 which allows for analysing issue competition throughout the entire electoral cycle. Press releases constitute an ideal instrument of political communication as political parties can independently choose what to communicate to their voters on a daily basis (see also Grimmer 2010;Hopmann et al 2012;Sagarzazu and Klüver 2015). Unlike speeches or questions in the legislature which are constrained by the parliamentary agenda, political parties can freely decide which political issues they want to emphasise.…”
mentioning
confidence: 99%
“…There is a rich literature that combines these factors using case studies, but it remains hard to generalize from those. This study demonstrates how government communication can be studied systematically (also see Sagarzazu and Klüver, 2017). On the longer term this allows for a more systematic evaluation of the interplay between economic problems, government communication, voter responses and policy changes.…”
Section: Resultsmentioning
confidence: 67%
“…As noted, poor economic performance makes the economy more salient and therefore governments may choose to "ride-the wave" of public opinion in their communication with the public. Recent research on European parties provides evidence for parties' attention to publicly salient issues in their press releases (Klüver and Sagarzazu 2016, see as well Sagarzazu and Klüver 2017) and party manifestos (Wagner and Meyer 2014). Also, the literature on American political campaigns has, by and large, confirmed that public salience is a more important predictor of the candidates' issue focus than issue ownership, and that issue trespassing and issue convergence are the norm (Sigelman and Buell 2004;Sides 2006;Druckman et al 2010 Alternatively, PMs may want to brag about good economic conditions.…”
Section: Issue Avoidance Versus Issue Engagementmentioning
confidence: 99%
“…4 See, e.g., Bakker et al 2015;Budge et al 2001. 5 See, e.g., Grimmer 2013;Grimmer, Westwood, and Messing 2015;Herzog and Benoit 2015;Pardos-Prado and Sagarzazu 2016;Proksch and Slapin 2015;Sagarzazu and Klüver 2017;Schwarz, Traber, and Benoit 2017. 6 Hoff, Raftery, and Handcock 2002;Hoff 2005. 7 That is, in a one-dimensional space, they are both placed to the left or the right of the zero point.…”
mentioning
confidence: 99%